Conducting a cost analysis to address issues of budget constraints on the implementation of the indoor residual spray program. an intervention to control and eliminate Malaria in two districts of Maputo Province, Mozambique - Canana, Neide Mércia de Orlando Hussene (Department of Public Health and Family Medicine, 2020)
Introduction: Over the past few years, the capacity of the government of Mozambique to sustain the cost of payment of salaries to operationalize the Indoor Residual Spray (IRS), a widely recommended tool to control and prevent malaria, is facing numerous challenges. This is due to recent restrictions of the Official Development Assistance (ODA), an external aid scheme and the main source of financing of the Mozambican government budget. Objective: The objective of this study was to estimate the cost of IRS operationalization activities in Matutuine and Namaacha districts health directorates, in Maputo Province, Mozambique. Methods: A cost analysis using an approach from the provider’s perspective was conducted in two district health directorates in the Maputo province, Matutuine and Namaacha. The institutions were purposely selected since in 2014 in both districts the expenditure on salaries to operationalize IRS was funded by the government budget. Cost information was collected retrospectively and both economic and financial costs were calculated. Uncertainty of results was tested using “one-way” deterministic sensitivity analysis. Results: The average total annual economic cost was 117,351.34 US$. The average economic cost per households sprayed totalled 16.35 US$. On average the economic costs per person protected is 4.09 US$ in total. In the financial analysis, the average total annual financial costs totalled 69,174.83 US$. The average financial cost per household sprayed and per person protected were 9.84 US$ and 2.46 US$ respectively. Vehicles, personnel salaries and consumables were the major substantial cost components. Conclusion: Setting aside the ODA restriction and focusing on the aim of implementing IRS within the existing resources, the study makessuggestions for improving efficiency by focusing on areas with a higher need and pays attention to cost drivers in order to reduce the costs.